MASKULINITAS DAN PRAKTIK TANGKAP LEPAS DALAM MEMANCING: SEBUAH KAJIAN TERHADAP SPORTFISHING - Gesang Manggala Putra (Lakon : Jurnal Kajian Sastra dan Budaya, 2014)
The absence of legal regulation in fishing activities has brought Indonesian waters to a serious degradation, especially in the population of game fish. The most reasonable solution to this problem is performing Catch and Release (CnR). However, very little has been explored regarding the activity of fishing and CnR in Indonesia. This study aims to identify masculinity traits in sportfishing as a masculine act. Furthermore, the result will hopefully be useful in designing an effective campaign for CnR. This study employs qualitative method to discover how sportfishing is produced and consumed, formulate the meaning of sportfishing to Indonesian anglers, and identify masculinity traits in the enactment and involvement of this activity. The study concludes that sportfishing is the new hegemonic masculinity, replacing the previous conventional fishing. It is a masculine bloc that inherits classic masculine traits and combines them with aspects of femininity, resulting in a new adaptive model of masculinity that sustains the patriarchal dominance toward subordinate masculinity and women.